2011
DOI: 10.1103/physrevb.83.094513
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Biroli-Mézard model: Glass transition and superfluidity in a quantum lattice glass model

Abstract: We study the quantum version of a lattice model whose classical counterpart captures the physics of structural glasses. We discuss the role of quantum fluctuations in such systems and in particular their interplay with the amorphous order developed in the glass phase. We show that quantum fluctuations might facilitate the formation of the glass at low enough temperature. We also show that the glass transition becomes a first-order transition between a superfluid and an insulating glass at very low temperature,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 68 publications
3
36
0
Order By: Relevance
“…In particular, we estimated the glass transition line and found that, as already reported in [27][28][29][30], quantum fluctuations promote glass formation. We critically discussed some issues related to our approach, in particular the role of exchange and a technical problem related to the kinetic energy.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In particular, we estimated the glass transition line and found that, as already reported in [27][28][29][30], quantum fluctuations promote glass formation. We critically discussed some issues related to our approach, in particular the role of exchange and a technical problem related to the kinetic energy.…”
Section: Discussionmentioning
confidence: 80%
“…Based on the combination of the present study and previous ones [27,28], we conjectured a phase diagram of dense metastable Helium 4 which is reported in Fig. 3 (left panel).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations